Manajemen Pembinaan Prestasi Futsal Kota Semarang dalam Persiapan Menghadapi PORPROV Jawa Tengah Tahun 2023 - Novari Putra, Ananda; Soegiyanto, Soegiyanto (Institut Teknologi Bandung, 2023)
Futsal is a sport that comes from Spanish, namely futbol sala, which is called indoor football, but in its development, futsal was not only done indoors but also outdoors; even on artificial turf, the sport could be played. Semarang is one of the cities that has very high interest in futsal, as evidenced by the enthusiasm of young people and adults for futsal events in the city of Semarang, one of which is the Central Java PORPROV (Inter-Provincial Sports Week) event in 2023. This research is included in qualitative research using descriptive data analysis techniques. The collection technique is a technique carried out by researchers when conducting research. The data collection techniques carried out in this study were observation, interview, and documentation techniques. fostering futsal achievements in Semarang City in the form of the Semarang City AFK League, starting from the U-17 age group to the U-19 age group. The AFK League in Semarang City itself has two divisions for men and one for women. The Semarang City AFK League has been running since the previous management. The conclusion in this study is that the management of achievement development has gone well, with support from management in the form of providing good facilities and infrastructure and recruiting trainers who are experienced and have certificates.